Otoritas Agama di Ruang Siber: Fragmentasi dan Kontestasi: - Hakim, Lukman; Mukhlis , Zainal (Jurnal Ilmu Komunikasi, 2023)
Internet which is able to integrate complex and diverse religious literature as well as is able to offer greater flexibility and accessibility to Muslim community (ummah), has become space for revolution in religious understanding and contestation of religious authority. This article focuses on how internet intervention is able to encourage religious authority fragmentated and contested in Indonesia. Using library research, this study argues that digital technology that offers greater flexibility and accessibility to Islamic texts can encourage Muslims to be less dependent on established sources of authority. This reality is exploited by pure-salafi and salafi-jihadist groups to promote individualising religious authority through independent mujtahid movement called "do it yourself" and "leaderless jihad". Meanwhile, the traditionalist-moderate Muslim group responded the salafi’s activism by building a religion narration regarding the importance of connected-sanad in doing ijtihad and studying religion which is disseminated through cyber media. In short, cyberspace has become a means of contestation of religious authorities in affirming religious identity and ideologyof moderate Muslims and radical conservative in particular.